ANALYSIS OF RESEARCH ON PHYSICAL CHEMICAL COMPOSITION AND CLASSIFICATION OF WOOL FIBER - Qarshiyev Davronjon Erkin o‘g‘li; Abdirashidov Xumoyiddin Abdumuxammad o‘g‘li; Davron Jurayev Amir o‘g‘li (Web of Journals Publishing, 2025)
This article analyzes the physico-chemical composition, structure, classification, types, fields of application and similar indicators of wool fiber.
Keywords: Wool, fiber, dirt, roughness, variety, grade, fineness